2019
DOI: 10.1007/s41048-019-00100-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular Ca2+/CaMKII signaling by TRPV4 membrane translocation during osteoblastic differentiation

Abstract: Bone constantly remodels between resorption by osteoclasts and formation by osteoblasts; therefore the functions of osteoblasts are pivotal for maintaining homeostasis of bone mass. Transient receptor potential vanilloid 4 (TRPV4), a type of mechanosensitive channel, has been reported to be a key regulator in bone remodeling. However, the relationship between TRPV4 and osteoblast function remains largely elusive. Only little is known about the spatial distribution change of TRPV4 during osteoblastic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…32,48 Mature osteoblasts have a higher TRPV4 expression as compared to immature osteoblasts, suggesting that TRPV4 expression increases during the osteoblast differentiation. 49,50 Mutations in TRPV4 are known to induce different channelopathies, where neuromuscular and/or skeletal dysplasia are common. 51 All of these indicate TRPV4 as an important molecular target for efficient bone healing.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,48 Mature osteoblasts have a higher TRPV4 expression as compared to immature osteoblasts, suggesting that TRPV4 expression increases during the osteoblast differentiation. 49,50 Mutations in TRPV4 are known to induce different channelopathies, where neuromuscular and/or skeletal dysplasia are common. 51 All of these indicate TRPV4 as an important molecular target for efficient bone healing.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bone repair needs tight regulation of Ca 2+ signaling and high metabolic states (i.e., mitochondrial homeostasis) of osteoblasts. Migration, proliferation, and differentiation of osteogenic cells are decisive for tissue repair, wherein an increase in the oxidative metabolism (mitochondrial bioenergetics) is necessary to awaken dormant cells and speed up this healing process. Reports suggest the importance of TRPV4 in maintaining Ca 2+ homeostasis within cells and within the mitochondria. , Mature osteoblasts have a higher TRPV4 expression as compared to immature osteoblasts, suggesting that TRPV4 expression increases during the osteoblast differentiation. , Mutations in TRPV4 are known to induce different channelopathies, where neuromuscular and/or skeletal dysplasia are common . All of these indicate TRPV4 as an important molecular target for efficient bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned observations open up possibilities for utilizing TRPV4 (including other TRP channels) as potential molecular target/s for bone-loss condition such as osteoporosis ( McNulty et al, 2015 ). Recently, it has been reported that during RCO differentiation, the expression and distribution of TRPV4 increases in the plasma membrane while decreases in the cytosol ( Hu et al, 2019 ). Our data further suggests that 4αPDD-mediated mineralization could be attenuated by RN1734, suggesting that TRPV4 activation-mediated functions were partly reversed by its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…47 TRPV4 is known to be able to directly activate CaM. 48 Whether or not the TRPV4-CaM pathway plays a direct role in VIC proliferation remains to be studied further. Here, we have shown that proliferation itself is dependent on microenvironment stiffness and suggest that mechanosensors other than TRPV4 are likely regulating proliferation.…”
Section: Discussionmentioning
confidence: 99%